Analisis Hukum Islam dan Hukum Positif Tentang Tindakan Aparat Negara Melakukan Spionase Terhadap Warga Negara - Asrudi; Mustafa, Zulhas'ari (Universitas Islam Negeri Alauddin Makassar, 2022)
This article aims to describe and analyze differences of opinion from the two legal bases, namely Islamic law and positive law regarding espionage by citizens against citizens. In answering the problems above, the author uses Library Research which is guided by the management of data obtained from several literatures. The sources of data obtained include secondary, primary and tertiary data. This research approach using a qualitative approach is something that is based on a literature study by exploring scientific works that are directly related to the object being studied and analyzing in the literature that has relevance to the problem discussed, then reviewing and then concluding. The results of this study indicate that there are differences and similarities in the views of Islamic law and positive law regarding the actions of state officials against citizens. In this paper, the opinion of Islamic law views that espionage carried out by state officials can be carried out if it is aimed at the interests of the State and Muslims. As the Prophet gave an example by sending trusted companions to spy on infidels and hypocrites who could endanger the security of Muslims at that time. However, apart from that, Islam strictly prohibits any spying if it is carried out on Muslims themselves, especially if the spying is groundless or only for personal gain as stated in the QS. Al-Hujurat paragraph 12. Then in positive law views that espionage may be carried out if the actions of the person who is the subject of spying has taken actions that are considered to violate the rules with sufficient preliminary evidence as regulated in the law relating to the permissibility of espionage. Outside of what is regulated in the law, espionage cannot be carried out because it violates a person's right to privacy as regulated in Law number 11 of 2008 concerning Information and Electronic Transactions